Folklor Indonesia dan Jepang: Suatu Studi Perbandingan - James Danandjaja (Antropologi Indonesia, 1991)
There are more similarities than differences in the development of folklore as a separated discipline in Indonesia and Japan. Folklore studies in Japan were started in 1930 while in Indonesia since 1972. As a result the Japanese has already developed their own theories and methods, while in Indonesia is still depending on the ones developed in Europe and United States. The similarities are both developed in order to look for their respected national identity. And it is interesting to note that there are many tale types and tale motifs that is similar in both countries.